Effect of Hemodialysis on Peripapillary Choroidal Thickness Measured by Swept-Source Optical Coherence Tomography. Issue 6 (June 2021) - Lee, Won June; Hong, Rimkyung; Kang, Min Ho; Cho, Heeyoon; Han, Sang-Woong; Yi, Joo-Hark; Shin, Yong Un; Seong, Mincheol
Abstract : Purpose: The aim was to investigate the effects of hemodialysis (HD) on peripapillary choroidal thickness (PCT) by swept-source optical coherence tomography and on other ophthalmologic parameters in patients with end-stage kidney disease. Materials and Methods: This was a prospective observational study. The authors evaluated 29 patients who underwent HD for end-stage kidney disease. Detailed ophthalmologic examinations and swept-source optical coherence tomography were performed immediately before and after HD. PCT was measured using the modification tool in the built-in OCT image viewer program. Changes in PCT before and after HD were statistically analyzed. Results: The average PCT significantly decreased from 127.3±49.2 μm before HD to 117.1±50.9 μm after HD ( P <0.001). A significant correlation was found between changes in PCT and macular choroidal thickness (ρ=0.547, P =0.002). Changes in mean ocular perfusion pressure did not significantly correlate with changes in PCT (ρ=−0.049, P =0.803). Conclusions: PCT significantly decreased after HD. HD could influence the optic nerve head and its surrounding structures. Abstract : Supplemental Digital Content is available in the text.